Emerging Gram negative resistance to last-line antimicrobial agents fosfomycin, colistin and ceftazidime-avibactam – epidemiology, laboratory detection and treatment implications. Issue 4 (3rd April 2018) - Sherry, Norelle; Howden, Benjamin
ABSTRACT: Introduction : Multidrug-resistant (MDR) and extensively-drug-resistant (XDR) Gram-negative bacteria have emerged as a major threat to human health globally. This has resulted in the 're-discovery' of some older antimicrobials and development of new agents, however resistance has also rapidly emerged to these agents. Areas covered : Here we describe recent developments in resistance to three of the most important last-line antimicrobials for treatment of MDR and XDR Gram negatives: fosfomycin, colistin and ceftazidime-avibactam. Expert commentary : A key challenge for microbiologists and clinicians using these agents for treating patients with MDR and XDR Gram negative infections is the need to ensure appropriate reference methods are being used to test susceptibility to these agents, especially colistin and fosfomycin. These methods are not available in all laboratories meaning accurate results are either delayed, or potentially inaccurate as non-reference methods are employed. Combination therapy for MDR and XDR Gram negatives is likely to become more common, and future studies should focus on the clinical effects of monotherapy vs combination therapy, as well as validation of synergy testing methods. Effective national and international surveillance systems to detect and respond to resistance to these last line agents are also critical.